(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Selection of appropriate weed management strategy helps reduce rice yield loss due to weeds. Despite some undesirable side-effects, no viable alternative is currently available to shift the chemical weed management in rice. However, time of herbicide application is very important with respect to its efficacy. Keeping in mind the inevitability of herbicidal weed control, the current study was designed to evaluate the response of selected aromatic fine rice varieties of Bangladesh to different herbicides based weed management practices compare to farmers’ practices. The experiment was conducted in a randomized complete block design with three replications. The experiment consisted of five aromatic rice varieties; Kalijira, BRRI dhan34, BRRI dhan37, BRRI dhan38 and Binadhan-13, and six different weed management practices comprising no weeding, weed free, mechanical + manual weeding, pre–emergence herbicide + manual weeding, post–emergence herbicide + manual weeding and pre– + post–emergence herbicide. Eleven weed species belonging to five families were observed in the experimental plots. Based on the summed dominance ratio (SDR), grassy weed species Echinochloa crusgalli (SDR of 30.7) was the most dominant species, whereas broadleaf weed Nymphaea nouchali (SDR of 0.83) was the least one. Among the weed control treatments, application of pre–+ post emergence herbicides offered the highest reduction in weed density and biomass at all sampling dates which resulted in minimum crop-weed competition facilitating improvement in the yield contributing characters and finally resulted in the highest grain yield (2.5 t ha−1) and harvest index (30.7%) next to the weed free treatment. The variety BRRI dhan38 gave the highest grain yield (3.4 t ha−1) due to the highest performance of the yield contributing characters among the varieties. In interaction, BRRI dhan38 with pre–+ post–emergence herbicide application gave the highest yield (3.4 t ha−1) apart from the weed free treatment. Being efficient in weed density and biomass reduction as well as the highest yield producer, sequential application of pre–and post–emergence herbicides may be recommended for effective weed management practices in BRRI dhan38 J. Bangladesh Agril. Univ. 16(1): 31-40, April 2018